Diagnostic circulating biomarkers to detect vision‐threatening diabetic retinopathy: Potential screening tool of the future?. Issue 3 (16th July 2021) - Frudd, Karen; Sivaprasad, Sobha; Raman, Rajiv; Krishnakumar, Subramanian; Revathy, Yeddula Rebecca; Turowski, Patric
Abstract: With the increasing prevalence of diabetes in developing and developed countries, the socio‐economic burden of diabetic retinopathy (DR), the leading complication of diabetes, is growing. Diabetic retinopathy (DR) is currently one of the leading causes of blindness in working‐age adults worldwide. Robust methodologies exist to detect and monitor DR; however, these rely on specialist imaging techniques and qualified practitioners. This makes detecting and monitoring DR expensive and time‐consuming, which is particularly problematic in developing countries where many patients will be remote and have little contact with specialist medical centres. Diabetic retinopathy (DR) is largely asymptomatic until late in the pathology. Therefore, early identification and stratification of vision‐threatening DR (VTDR) is highly desirable and will ameliorate the global impact of this disease. A simple, reliable and more cost‐effective test would greatly assist in decreasing the burden of DR around the world. Here, we evaluate and review data on circulating protein biomarkers, which have been verified in the context of DR. We also discuss the challenges and developments necessary to translate these promising data into clinically useful assays, to detect VTDR, and their potential integration into simple point‐of‐care testing devices.